Thermodynamic and Economic Analysis of Cargo Boil-Off Gas Re-Liquefaction Systems for Ammonia-Fueled LCO2 Carriers - Jun-Seong Kim; Do-Yeop Kim (Journal of Marine Science and Engineering)
In this study, cargo boil-off gas (BOG) re-liquefaction systems for ammonia-fueled liquefied carbon dioxide (LCO2) carriers were analyzed. These systems use cold energy from ammonia to reliquefy the CO2 BOG. In this study, a system that can completely reliquefy the CO2 BOG at all engine loads using only one heat exchanger is proposed, instead of the existing cascade system that requires multiple components. R744, which has a low global warming potential, was used as the working fluid for the refrigeration cycle in the CO2 BOG re-liquefaction system. The organic Rankine cycle (ORC) was used to reduce the net power consumption of the system. The existing and proposed systems were classified into Case 1 (existing system), Case 2 (our proposed system), and Case 3 (Case 2 combined with an ORC). Thermodynamic and economic analyses were conducted. Case 2 is a system with a simpler configuration than Case 1, but it has a similar thermodynamic performance. Case 3 has a higher exergy destruction rate than Cases 1 and 2, owing to the ORC, but it can significantly reduce the net power consumption. The economic analysis shows that Cases 2 and 3 reduce the total annual costs by 17.4% and 20.1%, respectively, compared to Case 1. The proposed systems are significantly more advantageous for long-term operation than existing systems.